1985
DOI: 10.3758/bf03200026
|View full text |Cite
|
Sign up to set email alerts
|

Different odors in rats from large and small rewards

Abstract: Although rats emit different odors in a goalbox upon receipt of unsignaled reward and nonreward, recent studies have failed to find odor differences from unsignaled large and small reward, apparently disconfirming the generalization that frustration-producing manipulations lead to a distinctive emission. Experiment 1 tested the hypothesis that providing discriminative runway signals, permitting subjects to anticipate the large and small rewards, would lead to different odor emissions. Results supported the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Laboratory studies have demonstrated the role of social factors in diet selection of rats and pointed to severa) ways in which rats can gain information about the palatability and utilisation of foods prior to trying them. These include intra-uterine exposure (Hepper, 1990), the flavour of the mother's milk, the presence of other individuals at feeding sites (Galef & Clark, 1972), the olfactory eues left at feeding sites (Galef & Heiber, 1976) and the olfactory information emanating from other adults (the « demonstrator effect », Ludvigson et al, 1985 ;Galef, 1988 ;Lavin et al, 1980).…”
Section: Social Lea Rningmentioning
confidence: 99%
“…Laboratory studies have demonstrated the role of social factors in diet selection of rats and pointed to severa) ways in which rats can gain information about the palatability and utilisation of foods prior to trying them. These include intra-uterine exposure (Hepper, 1990), the flavour of the mother's milk, the presence of other individuals at feeding sites (Galef & Clark, 1972), the olfactory eues left at feeding sites (Galef & Heiber, 1976) and the olfactory information emanating from other adults (the « demonstrator effect », Ludvigson et al, 1985 ;Galef, 1988 ;Lavin et al, 1980).…”
Section: Social Lea Rningmentioning
confidence: 99%
“…Such an odor might arise either because the DEN was a novel taste in the runway environment or, perhaps more plausibly, because DEN was a reward of lesser value in comparison with water (cf. Ludvigson et al, 1985). This explanation leads to the expectation that such odors might accumulate over successive subjects, resulting in a progressively greater slowing of speeds over initial subjects.…”
Section: Runway Datamentioning
confidence: 99%
“…When one odor signals R and the other odor signals N, approach to the goal area is eventually slower in the presence of the signal of N, regardless of which odor provides the signal (Eslinger & Ludvigson, 1980). Furthermore, rats emit odors in anticipation of goal events such as R and N, and the emissions appear to differ for large and small rewards when both are experienced by the emitting rat (Ludvigson, Mathis, & Choquette, 1985). More recently, research has shown that in addition to acting as discriminative stimuli, such odors can also act as conditioned stimuli in a conditioned odor aversion procedure where they signal impending illness (Batsell & Ludvigson, 1989).…”
mentioning
confidence: 99%
“…Numerous experiments have suggested that laboratory rats emit different odors into their environment during or in anticipation of goals of different value, such as reward (R) and nonreward (N), and that these odors are readily discriminated by other rats (e.g., Ludvigson, 1969;Ludvigson, Mathis, & Choquette, 1985;Ludvigson & Sytsma, 1967;McHose & Ludvigson, 1966;Mellgren, Fouts, & Martin, 1973;Morrison & Ludvigson, 1970;Prytula & Davis, 1974;Prytula, Davis, & Fanning, 1981;Taylor & Ludvigson, 1980). As a tactic of experimental efficiency, most studies have demonstrated discrimination by having odor arising from N (N odor) signal nonreward and odor arising from R (R odor) signal reward.…”
mentioning
confidence: 99%